2008
DOI: 10.1212/01.wnl.0000316392.55784.57
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin half-life and clearance during maintenance therapy in adults and elderly patients with epilepsy

Abstract: Healthy elderly adults appear to have the same phenytoin (PHT) pharmacokinetics as younger adults. Reduced PHT dosage requirements may be due to age-related changes in patients' sensitivity to the therapeutic and toxic effects of the drug. The prolonged elimination half-life suggests that most patients can take PHT once daily and the time to reach steady-state may extend to 2-3 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
(59 reference statements)
1
24
0
Order By: Relevance
“…Our findings showed that the plasma concentrationtime curve for phenytoin was fitted using a 1-compartment open model with linear absorption and MichaelisMenten elimination that corroborated previous studies [17,18]. We estimated the V max and K m parameters in our population, which is very critical for personalizing the phenytoin dosage.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings showed that the plasma concentrationtime curve for phenytoin was fitted using a 1-compartment open model with linear absorption and MichaelisMenten elimination that corroborated previous studies [17,18]. We estimated the V max and K m parameters in our population, which is very critical for personalizing the phenytoin dosage.…”
Section: Discussionsupporting
confidence: 88%
“…Data from pharmacokinetic analysis in old patients taking phenytoin revealed aging is associated with a gradual decline in AED clearance 34 . Furthermore, as serum albumin level falls gradually with each decade of age 35 , relatively lower phenytoin doses and lower plasma concentrations can be adequate for satisfactory seizure control in elderly patients 36,37 . The therapeutic window needs to be narrowed down in elderly patients.…”
Section: Pharmacological Changes Of Aeds In the Elderlymentioning
confidence: 99%
“…Because of the complexity of confounding variables and the lack of correlation between simple measures of liver function and drug metabolism, the effect of age on hepatic drug metabolism remains largely unknown [21]. Interestingly, genetic determinants of hepatic isoenzymes may be more important than age in determining a person's clearance [22].…”
Section: Choosing the Right Aedmentioning
confidence: 99%
“…A recent study suggested that metabolism does not decrease greatly with age in healthy elderly. Using stable-labeled (nonradioactive) phenytoin to very precisely measure the phenytoin clearance, one study found that advancing age was not as much of a factor as had been previously reported [32]. A range of 5-15 mg/L total may be more appropriate as a therapeutic range for the elderly due to abnormal protein binding [33].…”
Section: Phenytoinmentioning
confidence: 99%